The Role of the Capital Market in Increasing Economic Growth in Indonesia - Lubis, Putri Kemala Dewi; Manalu , Christin Lince Natalia; Lubis, Atika Atayarisah; Tambunan, Laura, Magdalena; Saputra, Firman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is entitled The role of capital markets in increasing economic growth in Indonesia. The aim of this research is to determine: 1) The contribution of the capital market in economic growth, 2) Trends in the capital market in Indonesia's growth 3) Opportunities and challenges faced by the capital market in Indonesia. In implementing a country's national economic development, funding is needed from the government and society, while one alternative source of funding is the capital market. The capital market is a place to trade securities issued by institutions and professions related to securities. The research method used was a literature review. The role of the capital market in national economic growth can be seen through its influence on macroeconomic indicators such as the real exchange rate, inflation rate and economic growth as measured by Gross Domestic Product. And the development of the capital market in Indonesia is moving positively, which can be reflected in the increase in public interest in investing in it. This can be observed from the growth in the number of investors registered with the Indonesian Central Securities Depository (KSEI) through single investor identification (SID).